Spherical Nucleic Acids for Topical Treatment of Hyperpigmentation - Fang Yang; Xueguang Lu; Dali Wang; Jiansong Cai; Yuyan Wang; Peiru Chen; Mengqi Ren; Hao Lü; Jennifer Union; Lei Zhang; Yehui Sun; Fei Jia; et al. (2021)
Oligonucleotide-based materials such as spherical nucleic acid (SNA) have been reported to exhibit improved penetration through the epidermis and the dermis of the skin upon topical application. Herein, we report a self-assembled, skin-depigmenting SNA structure, which is based upon a bifunctional oligonucleotide amphiphile containing an antisense oligonucleotide and a tyrosinase inhibitor prodrug. The two components work synergistically to increase oligonucleotide cellular uptake, enhance drug solubility, and promote skin penetration. The particles were shown to reduce melanin content in B16F10 melanoma cells and exhibited a potent antimelanogenic effect in an ultraviolet B-induced hyperpigmentation mouse model.